Prevalence of Hepatitis B Virus and Associated Factors Among Pregnant Mothers Attending Antenatal Care in Public Hospitals, Afar Region, North Eastern Ethiopia - Edris, Hussen; SREEMANARAYANA , V. (YCAB Publisher, 2024)
Background:Hepatitis B kills a large number of individuals every year all over the world. Despite the critical nature of this issue, the extent of hepatitis B virus infection among pregnant women in the Afar Region remains unknown. Therefore, this study aimed to assess the Prevalence of the Hepatitis B Virus and its associated factors among pregnant women Attending Antenatal Care in Public Hospitals in Afar, Ethiopia. Method:A hospital-based cross-sectional study was conducted from August 1, 2023, to August 2, 2024, involving 442 pregnant women attending antenatal care at five public hospitals in the Afar Region. Structured and pretested questionnaires were used to collect socio-demographic data and associated factors. Blood samples were collected from each consenting participant after the interviews to assess their HBV status. The data was analyzed using SPSS, applying bivariate and multivariable logistic regression methods to identify associations and determine statistical significance, with a p-value threshold of less than 0.05. Result:The overall Prevalence of hepatitis B virus infection was 12.7% (95% CI: 9.7-16.1). Hepatitis B virus infection had a significant association with a family history of the virus (AOR=3.92; 95% CI [1.26-12.14]), sharing sharp objects (AOR=3.83; 95% CI [1.16-12.6]), female genital mutilation (AOR=4.77; 95% CI [1.02-22.3]), extraction of teeth (AOR=5.22; 95% CI [2.54-10.7]), and hospital admissions (AOR=2.48; 95% CI [1.15-5.35]). Conclusion:This study revealed a high prevalence of HBV in specific public hospitals in Ethiopia's Afar regional state. The study found that a history of Hepatitis B virus in the family, sharing of sharp objects, having teeth extraction, hospital admission, and female genital mutilation are important risk factors that lead to the high viral Prevalence in the Afar Region. Establishing comprehensive prenatal screening programs, educating the public, and considering cultural considerations are essential to solving this public health issue. Keywords: hepatitis B prevalence; pregnant women; antenatal care; public hospitals, Ethiopia